Independence Requirement Analysis for Common-Mode Analysis of Aircraft System Safety Based on AADL - Hongze Ruan; Fan Qi; Xiaohui Wei; Yadong Zhou; Zhong Lu (Aerospace, 2025)
Common-mode analysis (CMA) is a qualitative analytical method used to support the evaluation of independence in the system safety assessment of civil aircraft. In traditional CMA, independence requirements are usually identified by evaluating the combination of events using the fault tree AND-gates. This approach is cumbersome and highly dependent on the skills and experiences of system safety engineers. An Architecture Analysis and Design Language (AADL)-based methodology is proposed to derive independence requirements for CMA. Error propagation data in AADL is extracted to develop a fault propagation model. Subsequently, potential factors contributing to common-mode failures (CMFs) are identified using the fault propagation model. A Primary Flight Computer (PFC) of an aircraft is used as a case study to illustrate the effectiveness of our proposed method.